The Effect of Addition Two Different Thickening Agent (Gelatine and Carrageenan) for Shelf Life and Physicochemical Properties In Grass Jelly - Nurul Atikah Ismail (2019)
Grass jelly agar and drink had been popular because of their nutrition especially high in dietary fibre and carbohydrates. There are some problem that can reduces consumer preferences and perception. This research was conducted to study the physicochemical analysis and shelf life in grass jelly made with two different thickening agent which are gelatine and carrageenan. This research was to determine appropriate percentage of addition gelatine and carrageenan. This study also conducted to improve the texture of grass jelly by addition of gelatine and carrageenan. Physicochemical properties which are pH, brix, colour and texture was analyse by weekly until week 4. Furthermore, shelf life of grass jelly with addition gelatine and carrageenan also will be evaluated. Grass jelly agar will be prepared with different percentage which are addition of gelatine 1%, 2%, 3% and 4% while addition of carrageenan 6%, 7%, 8% and 9%. The samples will be kept at constant temperature which is 4 0C for 3 months. In order to test the shelf life, the parameters including pH, texture, colour and concentration of brix at week 1 will be determined, to select the best percentage of gelatine and carrageenan for microbiological analysis. The shelf life will be tested within 3 months on weekly basis and all parameters will be test weekly. Based on the result, shelf life of grass jelly addition with gelatine is much longer than carrageenan. Physicochemical analysis showed that grass jelly with addition of gelatine at the percentage 3% and addition carrageenan at 7% is the most preferable sample. In future study, another thickening agent can be used to replace with gelatine and carrageenan for another analysis.